The Influence of Digital-Based Training and Technical Competence on Human Resource Competitiveness Through Technology Readiness at PT PLN (Persero) ULP Dumai City - Edy Saputra; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to explore how digital-based training and technological skills impact human resource competitiveness, with technological readiness as a mediating factor at PT PLN (Persero) ULP Dumai Kota. A quantitative methodology was employed for this study, employing a survey approach. The participant group consisted of 80 workers selected through a saturated sampling method. The data were processed and analyzed using Partial Least Squares (PLS) techniques. The results indicate that digital training and technical skills positively and significantly influence human resource competitiveness. Furthermore, both factors positively and significantly influence technological readiness. However, technological readiness did not significantly impact human resource competitiveness and therefore did not serve as a mediating factor in the relationship between digital training and technical skills on human resource competitiveness. This research is expected to contribute to the advancement of human resource management, particularly in enhancing employee competitiveness by focusing on improving digital training and strengthening technical skills.